Gadoxetic acid‐enhanced magnetic resonance imaging reflects co‐activation of β‐catenin and hepatocyte nuclear factor 4α in hepatocellular carcinoma. Issue 2 (13th June 2017) - Kitao, Azusa; Matsui, Osamu; Yoneda, Norihide; Kozaka, Kazuto; Kobayashi, Satoshi; Koda, Wataru; Minami, Tetsuya; Inoue, Dai; Yoshida, Kotaro; Yamashita, Taro; Yamashita, Tatsuya; Kaneko, Shuichi; et al.
Abstract : Aim: The aim of this study is to clarify the correlation of the co‐activation of β‐catenin and hepatocyte nuclear factor (HNF)4α with the findings of gadoxetic acid‐enhanced magnetic resonance imaging (MRI), organic anion transporting polypeptide (OATP)1B3 expression, and histological findings in hepatocellular carcinoma (HCC). Methods: One hundred and ninety‐six HCCs surgically resected from 174 patients were enrolled in this study. The HCCs were classified into four groups by immunohistochemical expression of β‐catenin, glutamine synthetase (GS), and HNF4α: (i) β‐catenin/GS (positive [+]) HNF4α (+); (ii) β‐catenin/GS (+) HNF4α (negative [−]); (iii) β‐catenin/GS (−) HNF4α (+); and (iv) β‐catenin/GS (−) HNF4α (−). We compared the four groups in terms of the enhancement ratio on the hepatobiliary phase of gadoxetic acid‐enhanced MRI, immunohistochemical organic anion transporter polypeptide (OATP)1B3 (a main uptake transporter of gadoxetic acid) expression and histological features, overall survival, and no recurrence survival. The Kruskal–Wallis test, Steel–Dwass multiple comparisons test, Fisher's exact test, and log–rank (Mantel–Cox) test were used for statistical analyses. Results: Enhancement ratio on gadoxetic acid‐enhanced MRI in HCC with β‐catenin/GS (+) HNF4α (+) was significantly higher than those of the other three groups ( P  < 0.001). The OATP1B3 grade was also significantly higher in HCC with β‐catenin/GS (+) HNF4α (+) ( P  < 0.001). Hepatocellular carcinoma with β‐catenin/GS (+) HNF4α (+) showed the highest differentiation grade as compared to the other groups ( P  < 0.004). There were no significant differences in portal vein invasion, macroscopic growth pattern, or prognosis analyses between the four groups. Conclusion: Co‐activation of β‐catenin and HNF4α would promote OATP1B3 expression, and consequently higher enhancement ratio on gadoxetic acid‐enhanced MRI and higher differentiation grade in HCC.